Implementing Benefit-Risk Assessment for the Periodic Benefit-Risk Evaluation Report. (May 2016) - Warner, Margaret R.; Wolka, Anne M.; Noel, Rebecca A.
Background: In 2012, the International Conference on Harmonisation (ICH) E2C (R1) guideline for periodic safety update reporting (PSUR) for medicines was revised. Several new concepts that expanded the scope of the report were added, including a new section focused on benefits and an additional section focused on integrated benefit-risk (B-R) assessment. These changes are reflected in the new title of the report, namely, the Periodic Benefit-Risk Evaluation Report (PBRER). Recently, structured frameworks have been developed by the pharmaceutical industry and regulatory agencies to facilitate B-R analysis for medicines. Methods: This manuscript provides suggestions for incorporating the elements of a structured B-R assessment into the PBRER and also includes practical approaches for implementing the ICH guidelines for the B-R analysis section. Results: The main components of a B-R assessment for the PBRER include decision context; key benefits and key risks; strengths, limitations, and uncertainties of the evidence; risk management; and the overall B-R conclusions. Conclusions: A structured, systematic approach to defining a medicine's B-R profile will help ensure compliance with this ICH objective for the PBRER.